Analysis of microtubules and F-actin structures in hyphae and conidia development of the opportunistic human pathogenic black yeast Aureobasidium pullulans - Kopecká, Marie; Gabriel, Miroslav; Takeo, Kanji; Yamaguchi, Masashi; Svoboda, Augustin; Hata, Kunihiko (Microbiology (Reading, England), 2003)
Organization of the cytoskeleton was studied in the ascomycetous black yeast Aureobasidium pullulans, an opportunistic human pathogen, in an effort to present it as a potential target of antifungal therapy. Long cytoplasmic microtubules, extending along the hyphae from the base to the growing apex, were the dominant structures in multinucleate interphase cells. Before mitosis these microtubules disappeared and were replaced by intranuclear spindles. This reorganization of microtubules occurred along the whole length of hypha before synchronous division of the nuclei. Actin cytokinetic rings were rarely seen. Cortical actin in the form of patches accumulated in areas of cell wall growth, i.e. in the hyphal apex and near the occasionally formed septum. Actin cables were not seen. During synchronous conidiogenesis, the cytoplasmic microtubules extended along developing conidia, and actin patches lined their subcortical areas. Actin rings were formed regularly at the base of uninuclear conidia. Microtubule inhibitor methyl benzimidazol-2-ylcarbamate disintegrated the microtubules, and inhibited nuclear division, development of hyphae and conidiogenesis. Actin inhibitor Cytochalasin D induced swelling of hyphal apexes and developing conidia. This inhibitory activity ceased after 5 to 12 h when the occasional septa appeared and conidiogenesis was completed. The lack of unicellular organization in multinucleate hyphae of A. pullulans seems be related to a rarity of F-actin structures: i.e. absence of actin cables, the lack of actin cytokinetic rings in particular, resulting in the uncoupling of the nuclear division from cytokinesis; the association of both processes is, however, retained during conidiogenesis.
Keywords: mikrotubuly; Fluorescent Antibody Technique, Indirect; Ascomycota; fluorescenční protilátková technika nepřímá; oportunní infekce; Microscopy, Electron; Microtubules; aktiny; Opportunistic Infections; mykózy; Actins; Cytoskeleton; Mycoses; cytoskelet; elektronová mikroskopie